Developing leadership skills for better people’s management / Hazwati Hashim - Hashim, Hazwati (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
What does it take to be a good leader and what is leadership? Leadership means forming and getting people involved in the same direction that he or she thinks is best for the organization. Either you are leading a class, a team or an organization, a leader must possess the qualities to be a great leader. To begin with, we need to understand the importance of leadership and its place in an organization. Leadership plays a vital role in managing people. Being a good leader takes responsibility in their leadership. This means that they understand well their responsibility which will affect the people they lead. Similarly, a good leader will have their followers in mind whenever they do anything. Having said that, as to ensure them to succeed as a leader, other than having a common trait such as good communication and showing highly committed in their job; the other quality that they must have to understand what the followers need from leaders.